Heavy metals in agricultural soils developed on diverse parent materials in Cross River State, Nigeria. Issue 10 (24th August 2021) - Afu, Marcus Sunday; Isong, Isong Abraham; Ene, Aki Emmanuel; John, Kingsley
ABSTRACT: This study investigated the current state and pollution loads of heavy metals in soils developed on diverse parent materials in southeastern Nigeria. Cu, Mn, Zn, Fe and Al were analyzed to estimate pollution loads and ecological risk of the area. The result showed soils developed on granite gneiss to have a higher concentration (measured in mg kg −1 ) of Cu (1.79), Mn (78.39) and Zn (28.53), while soils developed on Biotite hornblende gneiss and quartz-mica-schist had a higher concentration of Fe (≥18) compared with other parent materials. The contamination factor for Fe, Zn, Mn and Cu was low, whereas Al was moderately to considerably contaminated except for soils in S2 (0.362), S3 (0.662), S6 (0.142), S9 (0.661), S11 (0.803) and S15 (0.499). The result of the pollution load index indicated an unpolluted condition (PLI < 1). Excluding Al, the soils were practically uncontaminated with Zn, Cu, Fe and Mn, based on the Geo-accumulation index and Quartz-mica-schist was enriched by Zn in S6 (1.325) and showed low ecological risk (Er < 40) and (IR < 150). Hence, the soils in the studied communities are still in a safe state to be used for crop cultivation without any fear of metal contamination.